Disgust - Kosmeyer, Carolyn (Filozofski vestnik, 2016)
Disgust is an emotion traditionally dismissed from aesthetic consideration because it seems to be so completely aversive that it cannot be positively employed in art. However, the history of art and – especially – contemporary graphic and cinematic arts arouse disgust as an indispensable element of appreciation. The nature of this appreciation and the character of the “pleasure” it contains is examined by considering Cindy Sherman's works and several other examples from television and film.